Dupuytren’s Contracture: Outcome of limited fasciectomy - Raj Chaurasia, Lok; Singh Bhandari, Prawesh; Pudasain, Pushkar; Kishor Nakarmi, Kiran (Nepal Orthopaedic Association Journal, 2024)
Introduction: Dupuytren’s contracture of the palm and hand, is a benign fibroproliferative disorder of the fascial tissue.The small finger is the most affected finger followed by the ring finger and others. There is no treatment for the disease,but several treatments are available for contracture correction like observation, splinting, injecting pharmacological drugs, radial fasciectomy, segmental fasciectomy, and limited fasciectomy. In the study, we evaluate the effectiveness of limited fasciectomy for contracture correction. Method: Limited fasciectomy was done under magnification under tourniquet control to attain no extension deficit. Splinting was done post-operatively for 3 months. Assessment of the cases was done at the beginning of treatment and at 2 years follow up using Brief Michigan Hand Score. Results: The small finger is the most affected finger followed by the ring finger. Bilateral hand involvement was seen in 21.7% of cases. A good hand score was seen at the end of 2 years despite extension lag occurring in a few cases(p<0.00). Delayed wound healing was the most common complication. No recurrence was seen at the end of 2 years. Conclusion: Limited fasciectomy is a good treatment option for Dupuytren’s contracture.